The PIN family of proteins in potato and their putative role in tuberization - Roumeliotis, Efstathios; Kloosterman, Bjorn; Oortwijn, Marian; Visser, Richard G.; Bachem, Christian W. (Frontiers in Plant Science, 2013)
The PIN family of trans-membrane proteins mediates auxin efflux throughout the plant and during various phases of plant development. In Arabidopsis thaliana, the PIN family comprised of 8 members, divided into ‘short’ and ‘long’ PINs according to the length of the hydrophilic domain of the protein. Based on sequence homology using the recently published potato genome sequence (Solanum tuberosum group Phureja) we identified ten annotated potato StPIN genes. Mining the publicly available gene expression data, we constructed a catalogue tissue specificity of StPIN gene expression, focusing on the process of tuberization. A total of four StPIN genes exhibited increased expression four days after tuber induction, prior to the onset of stolon swelling. For two PIN genes, StPIN4 and StPIN2, promoter sequences were cloned and fused to the GUS reporter protein to study tissue specificity in more detail. StPIN4 promoter driven GUS staining was detected in the flower stigma, in the flower style, below the ovary and petals, in the root tips, in the vascular tissue of the stolons and in the tuber parenchyma cells. StPIN2 promoter driven GUS staining was detected in flower buds, in the vascular tissue of the swelling stolons and in the storage parenchyma of the growing tubers. Based on our results, we postulate a role for the StPINs in redistributing auxin in the swelling stolon during early events in tuber development.